Bagaimana Pengaruh dari Kebijakan Pemerintah Dalam Mengendalikan Impor Terhadap Penurunan Tingkat Inflasi di Indonesia - Salsabila, Maysa; Hasanah, Fadhilatul; Amalia, Rika; Rahmah, Fitria (Journal of Business and Economics Research (JBE), 2024)
Inflation in Indonesia tends to be stable at around 5 percent over the last 6 years from various aspects of the economy, one of which is import activities where Indonesia is a world consumer. This is due to production limitations which influence fluctuations in prices of products and services. Based on this, the aim of this research is to find out how the government's actions regarding import control policies influence the inflation rate in Indonesia. The methodology used is quantitative with associative descriptive analysis, with multiple linear regression analysis techniques (time series data), and uses secondary data in the form of import value, import weight and inflation for the 2017-2022 period. The results of this research also show that the value of imports has a significant effect on inflation in Indonesia in 2017-2022, this is because if a country carries out import activities it will have an impact on increased foreign currency exchange which can then have an impact on inflation. Meanwhile, the weight of imports does not have a significant influence on inflation in Indonesia in 2017-2022, this is because if the price of imported goods rises, the majority of people are reluctant to buy goods abroad because the costs of obtaining them are also high. Then this had an effect on reducing inflation in Indonesia. However, in this condition, these two variables simultaneously have a significant influence on inflation, because the two variables are interconnected, where the higher the import value, the closer the two indicators are. If the value of imports increases, it can have an impact on reducing the volume of goods to be imported and vice versa, which will then affect inflation.